Perlindungan Hukum Terhadap Korban Kekerasan Seksual Di Perguruan Tinggi: Kajian Regulasi Dan Upaya Pemulihan Korban - Inez Lona Br Karo Sekali; Junita Friska; Lisnawaty Br Marbun; Saulina Siagian (Universitas Negeri Medan, 2026)
Sexual violence in higher education is increasingly rampant, threatening victims' physical, mental, and academic well-being. Despite its fatal impacts, most cases go unreported due to social pressure, stigma, fear of revictimization, and a lack of trust in institutional protection systems. This study examines the triggering factors of sexual violence such as patriarchal power imbalances its consequences, and the role of regulations in protecting victims in Indonesia. The results emphasize the need for the effective implementation of Law No. 12 of 2022 (UU TPKS) and the Minister of Education, Culture, Research, and Technology Regulation No. 30 of 2021. Furthermore, it highlights the importance of the massive establishment of PPKS Task Forces, the optimization of state institutions (Komnas Perempuan and KPAI), and the strengthening of student solidarity to create a campus environment that is safe and responsive to victim recovery.